Understanding Inappropriateness in Health Care: The Role of Supply Structure, Pricing Policies and Political Institutions in Caesarean Deliveries - Maura Francese; Massimiliano Piacenza; Marzia Romanelli; Gilberto Turati (European Regional Science Association (ERSA), 2011)
The upward trend in the incidence of caesarean deliveries is a widespread stylised fact in many countries. Several studies have argued that it does not reflect, at least in part, patients' needs but that it is also influenced by other factors, such as providers/physicians incentives. Not surprisingly, the incidence of caesarean sections is often used as an indicator of the degree of (in)appropriateness in health care delivery, which has also been found to be strongly correlated with expenditure differentials between regions. We exploit the significant regional variation in the share of caesarean deliveries in Italy to explore the impact on inappropriateness of three groups of policy variables: 1) political economy indicators (as a way to capture different approaches to the governance of the health care sector); 2) reimbursement and pricing policies (as DRG fees); 3) structural supply indicators (such as the incidence of private providers and the number of employees). The analysis controls for the demographic characteristics of patients and their education levels. Results suggest that tariffs might be an effective policy tool to control inappropriateness; however, the structure of the regional health care system matters. More importantly, also some characteristics of the regional governments and the financing mechanisms play a role.
Keywords: 330